Your small, important, place in the world - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Spore may have more than one million readers, but compared with the world s total population, it is just a tiny sliver. And even compared with the population of all ACP countries together (for whom, by whom, with whom Spore is produced), it s...